2021
DOI: 10.3390/nu13103425
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a 6-Month Lifestyle Intervention on Diet, Physical Activity, Quality of Life, and Markers of Cardiometabolic Health in Women with PCOS and Obesity and Non-PCOS Obese Controls: One Size Fits All?

Abstract: Little is known about the difference in effectiveness of lifestyle intervention between women with PCOS and non-PCOS women. In a post hoc longitudinal analysis of a randomized, controlled trial, we aimed to investigate whether infertile women with PCOS and obesity (N = 87) responded differently to a 6-month lifestyle intervention program than infertile non-PCOS obese controls (N = 172). We evaluated several aspects of the intervention such as changes in diet, physical activity, and dropout rate, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
2
14
1
Order By: Relevance
“…These findings are in contrast to previous studies on women with obesity and PCOS, in which weight loss led to improvement in several domains of the SF-36 15 , 49 . However, a more recent study of HRQoL in women with severe obesity showed no difference in improvement between women with and without PCOS after weight loss 50 .…”
Section: Discussionmentioning
confidence: 89%
“…These findings are in contrast to previous studies on women with obesity and PCOS, in which weight loss led to improvement in several domains of the SF-36 15 , 49 . However, a more recent study of HRQoL in women with severe obesity showed no difference in improvement between women with and without PCOS after weight loss 50 .…”
Section: Discussionmentioning
confidence: 89%
“…The participants in this study presented with low levels of SHBG, which is often related to hyperandrogenism (also present in the participants in this study). The association between physical activity or cardiovascular fitness might be mediated, in part, through androgens; however, this has only been studied in men [27]. Findings from a systematic review about exercise effects on hormones suggest that SHBG was largely unaffected by aerobic exercise but increased with either the isolated use of resistance training or the combination of cardiovascular and resistance exercise [28].…”
Section: Sex Hormone Binding Globulin (Shbg)mentioning
confidence: 99%
“…Researchers have explored lifestyle interventions that included energy-restricted diets and exercise in individuals with PCOS with overweight and obesity (Table 2). The interventions included in this review differ in the amount of energy restricted, with energy deficits ranging from 500-800 kcal/day deficit [100][101][102][103][104] or total energy intakes ranging between 1000-1400 kcal/day [105][106][107]. The exercise components also varied and consisted of individualized exercise programs [100][101][102], structured exercise training programs [103,106], and general exercise recommendations [104,105,107].…”
Section: Energy Restriction and Exercisementioning
confidence: 99%